2010
DOI: 10.1099/mic.0.043257-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal microbiota in irritable bowel syndrome: present state and perspectives

Abstract: Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder that has been associated with aberrant microbiota. This review focuses on the recent molecular insights generated by analysing the intestinal microbiota in subjects suffering from IBS. Special emphasis is given to studies that compare and contrast the microbiota of healthy subjects with that of IBS patients classified into different subgroups based on their predominant bowel pattern as defined by the Rome criteria. The current data availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
134
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(143 citation statements)
references
References 56 publications
4
134
0
5
Order By: Relevance
“…The last two of these were associated with changes in microbiota composition, but interestingly, no pattern of alteration was demonstrated [6][7][8][9][10]. Recent studies showed that the expression of the leukocyte antigen DQ2 is a strong risk factor for the development of celiac disease.…”
Section: Microbiota Health and Diseasesmentioning
confidence: 99%
“…The last two of these were associated with changes in microbiota composition, but interestingly, no pattern of alteration was demonstrated [6][7][8][9][10]. Recent studies showed that the expression of the leukocyte antigen DQ2 is a strong risk factor for the development of celiac disease.…”
Section: Microbiota Health and Diseasesmentioning
confidence: 99%
“…Recently, published data on the microbiota in IBS patients without a specifi ed history of a precipitating infection have not identifi ed a microbiotal " signature " other than a frequent reduction in Lactobacillus species. However, an emerging trend is a reduction in bacterial diversity and instability of the microbiota over time (for review see Salonen et al ( 29 )) Th e latter is of potential importance in that animal-based studies have shown that perturbation of a previously stable microbiota leads to changes in gut function ( 30 ) and behavior ( 31 ). Th e latter may be important given the association of psychiatric morbidity with postinfectious IBS.…”
Section: Pathophysiology Of Postinfectious Ibsmentioning
confidence: 99%
“…and Veillonella sp., have been reported. Quantitative and qualitative microbial alterations in the GI tract of IBS subjects may have a functional role in the syndrome aetiology or merely reflect the status of the gut, but still have diagnostic or prognostic value in clinical practise and research (Kassinen, 2009; www.intechopen.com Salonen et al, 2010). In the following chapter, these IBS-related alterations within the human GI microbiota are reviewed.…”
Section: Introductionmentioning
confidence: 99%